Peripheral Ossifying Fibroma in the Oral Cavity: MRI Findings - Swapnali Chaudhari; Hemant R. Umarji (Hindawi Limited, 2011)
The peripheral ossifying fibroma, a benign gingival overgrowth, occurs mainly in the anterior portion of the maxilla in young adults. The size of the lesion is usually less than 1.5 cm. We report a case of peripheral ossifying fibroma overlying the mandibular alveolar ridge of a 55-year-old female. MR scans showed a large exophytic soft tissue mass overlying mandibular alveolar ridge. The tumor revealed peripheral calcifications with slight erosion of adjacent cortical plate.